Hubungan Pus yang Tidak Ber-Kb dengan Kejadian Stunting pada Balita di Puskesmas Sikumana Kota Kupang - Angela Lovendra Naingalis; Sinta Inriani Olla (Malahayati Nursing Journal, 2025)
ABSTRACT Stunting continues to be a chronic nutritional issue in Indonesia, affecting children's growth and development. Short birth intervals indicate that a mother's organs have not completely recovered. Pregnancies with short birth intervals result in inadequate maternal nutrition, diminishing the mother's ability to support foetal growth. This can lead to impaired fetal development and an increased risk of low birth weight (LBW), which is associated with a higher risk of stunting. Family planning programs, which focus on couples of reproductive ages, emphasize the importance of managing birth intervals and having an ideal number of children. These programs encourage couples to space their first and second births by 36-48 months and to have two children ideally. The purpose of this study is to examine the relationship between couples of reproductive ages (CRA) who do not use family planning and the incidence of stunting in children under five at the Sikumana Health Center. The study used a retrospective cross-sectional design. The dependent variable was CRA not using family planning, and the independent variable was stunted children. The study included 50 CRAs who did not use family planning and were selected through purposive sampling. The chi-square statistical analysis depicted a p-value of 0.003 (p 0.05), leading to the rejection of the null hypothesis (Ho). The results of this research are that there is a significant relationship between PUS not having family planning and the incidence of stunting in toddlers at the Sikumana Health Center. Conclusion: It is necessary to provide education to increase the use of contraceptives in PUS to reduce stunting rates in children under five. Keywords: Children Under Five, Couples of Childbearing Age, Family Planning Program, Stunting.  ABSTRAK Stunting masih menjadi masalah gizi kronis yang mempengaruhi pertumbuhan serta perkembangan anak di Indonesia. Jarak kelahiran yang dekat menggambarkan fungsi dari organ-organ tubuh ibu belum pulih secara sempurna. Kehamilan dengan jarak kelahiran yang dekat menyebabkan tidak terpenuhinya nutrisi ibu, kemampuan ibu dalam memfasilitasi pertumbuhan janin akan berkurang dan mengakibatkan terhambatnya pertumbuhan janin serta berpengaruh  terhadap  kelahiran  BBLR. Bayi yang lahir dengan BBLR beresiko terhadap  stunting.  Mengendalikan  selang  waktu  kelahiran  dan  mewujudkan jumlah anak yang ideal merupakan salah satu program KB yang dimana targetnya  adalah Pasangan   Usia  Subur.  PUS mampu mengatur jarak antara kelahiran pertama dengan kelahiran  kedua pada rentan 36-48  bulan dengan jumlah anak adalah cukup dua. Tujuan penelitian adalah menganalisis hubungan PUS yang tidak ber-KB dengan kejadian stunting pada balita di Puskesmas Sikumana. Metode penelitian  yang  digunakan  adalah  cross  sectional   retrospektif. Variabel dependentnya adalah PUS yang tidak ber-KB, variabel independentnya adalah stunting. Sampel terdiri dari 50 PUS  yang dipilih melalui purposive sampling. Analisis statistik yang dilakukan dengan menggunakan uji analisis chi square menghasilkan nilai p sebesar 0,003 (p0,05), yang menunjukkan penolakan hipotesis nol (Ho). Hasil penelitian ini yaitu ada hubungan yang signifikan antara PUS tidak ber KB dengan kejadian stunting pada balita  di Puskesmas Sikumana. Simpulan perlunya memberikan edukasi guna meningkatkan penggunaan alat kontrasepsi pada PUS untuk menurunkan angka stunting pada balita. Kata Kunci: Balita, Keluarga Berencana, PUS, Stunting